"No queers out there"? Metronormativity and the queer suburban. Issue 9 (9th June 2020) - Podmore, Julie A.; Bain, Alison L.
Abstract: Despite past projects to "decentre" metronormativity—a societal bias toward queer urban imaginings—in geographical scholarship, attention to suburbia has been limited due, in part, to reliance upon, and reinforcement of, an urban–rural binary that disqualifies the metropolitan periphery. This paper unpacks this binary by reviewing key themes at the intersections of the queer and suburban within the subfields of geographies of sexualities and queer geographies. It begins by outlining the American metronormativities critique and evaluating the claim that the "non‐metropolitan" should be the primary arena for unsettling the queer urban. Four key themes from the Anglo‐American‐Australian literature on the queer suburban are then surveyed: suburbanization processes, suburban relocations, suburban "ways of life, " and suburban home‐making. Having evaluated the current state of the subfield, the paper concludes by pointing to the possibilities of the queer suburban for future urban geography and geographies of LGBTQ+ sexualities scholarship.